Astragalus protects PC12 cells from 6-hydroxydopamine-induced neuronal damage: A serum pharmacological study - Li-Ying Guo; Feng-Lei Shi; Meng Li; Jin-Hao Sun; Chuan-Gang Li; Zeng-Xun Liu (Chinese Journal of Physiology, 2021)
Accumulating evidence has already indicated that traditional Chinese medicine (TCM) possesses tremendous potential for treating neurodegenerative diseases. Astragalus, also named Huangqi, is a famous traditional medical herb that can be applied to treat cerebral ischemia and prevent neuronal degeneration. Nevertheless, the underlying mechanisms remain largely unexplored. In the present study, Astragalus-containing serum (ASMES) was prepared and added into the culture medium of PC12 cells to explore its neuroprotective effect on 6-hydroxydopamine (6-OHDA)-caused neuronal toxicity. Our data showed that ASMES significantly ameliorated the cellular viability of cultured PC12 cells against the neurotoxicity induced by 6-OHDA (P < 0.05). Moreover, ASMES significantly decreased the cell apoptosis triggered by 6-OHDA (P < 0.01). Furthermore, 2′,7′-dichlorofluorescin diacetate assay was performed to detect the changes in oxidative stress, and we showed that 6-OHDA elevated the production of reactive oxygen species (ROS), whereas ASMES significantly reversed these changes (P < 0.01). Besides, mitochondrial membrane potential (MMP) assay showed that ASMES could restore 6-OHDA-damaged MMP in cultured PC12 cells (P < 0.05). In conclusion, Astragalus could protect PC12 cells from 6-OHDA-caused neuronal toxicity, and possibly, the ROS-mediated apoptotic pathway participated in this process. Collectively, our findings provided valuable insights into the potential in treatment of neurodegenerative diseases.